لترقية قدرة الطلبة على مهارة الكلام TeamTeaching تطبيق أسلوب - Safitri, Aida; Ninoersy, Tarmizi; Fajriah, Fajriah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2021)
According to the researcher’s on Arabic teaching conducted in the class X-l MAN 4 Pidie Jaya the students were able to speak Arabic well. They perceived that speaking Arabic was difficult. In addition, the teachers who taught the Arabic did not use the appropriate methods . As a result, the students were not engaged and felt bored during the teaching and learning process. The students were sleeping, playing and annoying their friends. The team teaching method is a method to fix all problems that occur both sides in students and teachers in the learning process. The aim of this research is to investigate the effectiveness of using team teaching method in improving students’ speaking ability and to find out student’s responses of using team teaching method in improving students’ speaking ability. The research method used was a pre experiment with one group pre test post test design. The research used pre-test and post test as well as ‘questionnaire as data collection instruments. The research found that the use of team teaching method was effective to increase students’ speaking ability.Furthermore, it was found that the result of T-Test calculation was bigger than T-Table 2,04<9,280<2,75. The result of student’s response sheets indicates that students have positive perception toward the use of team teaching method in speaking teaching. It was reflected in the student’s scrores in which 95,5% of them who interested in the teaching of speaking using team teaching method.